The Legal System of the All-You-Can-Eat Ticket System at Tlogo Argo-Tourism, Indonesia: A Maṣlaḥah al-Mursalah Perspective - Norma Siamtina, Desi; Chairul Huda, Muhammad; Ma’mun, Sukron; Nastangin, Nastangin (Journal of Islamic Law, 2023)
This article analyzes the legal system in the all-you-can-eat ticket system of Tlogo argo-tourism in Central Java, Indonesia. This research is based on recent concerns over the system’s implementation, specifically regarding its lack of clarity (gharar). The study employs a qualitative approach, combining legal-empirical analysis with the legal system theory of Lawrence Friedman and the concept of maṣlaḥah al-mursalah (public interest). The findings show that the all-you-can-eat ticket system in Tlogo argo-tourism has three components required by Lawrence Friedman’s legal system theory: legal structure, legal substance, and legal culture. The legal culture component is crucial in implementing the all-you-can-eat ticket system internally and externally. Moreover, the system also fulfills the three elements of maṣlaḥah al-mursalah: maṣlaḥah ḍaruriyyah (primary public interest), maṣlaḥah ḥajiyyah (tertiary public interest), and maṣlaḥah tahsiniyah (tertiary public interest). Therefore, this study contributes to a wider and more comprehensive view of buying and selling practices from the legal system’s perspective and maṣlaḥah al-mursalah.